Researcher development in universities: Origins and historical context (UCL Press, 2019)
This article explores the origins of researcher development in British universities. Its principal aim is to provide a coherent, and reasonably succinct, account of the evolution and development of researcher development that is as consistent as possible with what is known about the development of the Western university, the history of the research doctorate and the emergence of the research university. The main conclusion is that the origins of researcher development in the modern university can be found in the philology of the early modern university, which in turn emerged from the accumulation of knowledge in Western Christendom from other places and other times. Other conclusions are that there was little researcher development in the medieval university, and that the 'traditional' model of researcher development, centred on the PhD, is much more recent than is commonly supposed, so that, from a long-term perspective, the 'traditional model' may be but one stage in its continuing development. The article also develops a model that locates researcher development within a series of intellectual contexts: from the research process itself, to the advancement of knowledge more generally, and, finally, to changes in conceptions of knowledge itself.